Analysis of Salted Fish Processing Production in Panipahan, Pasir Limau Kapas District, Riau Islands - Ranawati; Nurintan Asyiah Siregar (PT FORMOSA CENDEKIA GLOBAL, 2024)
This research was conducted in early May 2024 in Panipahan, Pasir Limau Kapas District, Rokan Hilir Regency, Riau Province. The purpose of this study was to analyze the process, input, and output in the analysis of salted fish processing production. In addition, it also determines investment and profit and analyzes the prospects and constraints of salted fish processing production. This research was conducted using a survey method by taking activities/case studies and determining respondents using the census method. From the results of the study, salted fish processing production activities in the form of input have sufficient availability, the process runs regularly so that it produces output in the form of processed salted fish products ready to be marketed. The total investment is IDR 78,464,000 per month and the profit is IDR 16,760,000 per month. According to various feasibility criteria, this business is feasible to be continued and developed